The 'Soda Tax' is Unlikely to Make Mexicans Lighter: New Evidence on Biases in Elasticities of Demand for Soda - Mabel Andalón; John Gibson (Institute of Labor Economics (IZA), 2017)
Mexico's 'soda tax' has been predicted to reduce average weights by two to four pounds, based on extant estimates of an own-price elasticity of quantity demand for soda of between -1.0 and -1.3. These estimates ignore consumer responses on the quality margin and correlated measurement errors. We use Mexican household budget survey data and city-level soda prices to estimate unrestricted demand models that correct for both errors. The corrected own-price elasticity of quantity demand is just -0.2 to -0.3, so tax-induced soda price increases might cut average weights by less than one pound, which is too small to improve health.
Keywords: D12; I10; 330; demand; household surveys; quality; price; soda taxes; Mexico